2013
DOI: 10.1371/journal.pone.0062497
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferases Interact with AMP-Activated Protein Kinase: Evidence for S-Glutathionylation and Activation In Vitro

Abstract: AMP-activated protein kinase (AMPK) is a cellular and whole body energy sensor with manifold functions in regulating energy homeostasis, cell morphology and proliferation in health and disease. Here we apply multiple, complementary in vitro and in vivo interaction assays to identify several isoforms of glutathione S-transferase (GST) as direct AMPK binding partners: Pi-family member rat GSTP1 and Mu-family members rat GSTM1, as well as Schistosoma japonicum GST. GST/AMPK interaction is direct and involves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…Although there is a degree of redundancy within the GST family, GSTP is the most highly expressed isozyme in MEF cells and BMDDC and influences the doubling time of these cells (39,61) and remains the only isoform to exhibit thiolase activity (28,51,52). Our present results show a significant difference in levels of innate resistance of the Gstp1/p2 +/+ and Gstp1/p2…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a degree of redundancy within the GST family, GSTP is the most highly expressed isozyme in MEF cells and BMDDC and influences the doubling time of these cells (39,61) and remains the only isoform to exhibit thiolase activity (28,51,52). Our present results show a significant difference in levels of innate resistance of the Gstp1/p2 +/+ and Gstp1/p2…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, loss of GRX2 can compromise mitochondrial respiration and ATP production and alter O 2˙− /H 2 O 2 production, which is associated with the development of heart disease, hypertension, cataracts, and perturbations in embryonic development. In addition to the glutaredoxin enzymes, it has also been found that glutathione S-transferase can catalyze the reversible S-glutathionylation of cellular proteins (Klaus et al, 2013). Pi and Mu-members of the GST family have been found to catalyze the S-glutathionylation of AMP kinase, the master energy gauge for the cell (Klaus et al, 2013).…”
Section: Controlling Mitochondrial Ros Production By Redox Signalsmentioning
confidence: 99%
“…In addition to the glutaredoxin enzymes, it has also been found that glutathione S-transferase can catalyze the reversible S-glutathionylation of cellular proteins (Klaus et al, 2013). Pi and Mu-members of the GST family have been found to catalyze the S-glutathionylation of AMP kinase, the master energy gauge for the cell (Klaus et al, 2013). It remains to be determined if GST isoforms are also required to catalyze these reactions in mitochondria.…”
Section: Controlling Mitochondrial Ros Production By Redox Signalsmentioning
confidence: 99%
“…However, the role of this GSTp S-glutathionylation or the interaction of GSTp with Prx proteins in facilitating Sglutathionylation of target proteins remains unknown. Nonetheless, mouse embryonic fibroblasts (MEFs) from GSTp Using a yeast two-hybrid assay, GSTp was reported to interact with AMP-activated protein kinase (AMPK), an interaction that occurs in vitro and in liver tissue lysates (108). In vitro, GSTp facilitates the S-glutathionylation of AMPK in the presence of low concentrations of GSH, and this Sglutathionylation enhances AMPK kinase activity independent of AMPK phosphorylation (108).…”
mentioning
confidence: 99%
“…Nonetheless, mouse embryonic fibroblasts (MEFs) from GSTp Using a yeast two-hybrid assay, GSTp was reported to interact with AMP-activated protein kinase (AMPK), an interaction that occurs in vitro and in liver tissue lysates (108). In vitro, GSTp facilitates the S-glutathionylation of AMPK in the presence of low concentrations of GSH, and this Sglutathionylation enhances AMPK kinase activity independent of AMPK phosphorylation (108). In addition, inhibition of GSTp in C10 murine alveolar epithelial cells with TLK-199 or siRNA blocks S-glutathionylation of the Fas ligand (FasL) in response to FasL stimulation (10), suggesting that GSTp plays a role in the FasL autoregulatory loop involving protein-S-glutathionylation.…”
mentioning
confidence: 99%